2009
DOI: 10.1371/journal.pone.0008188
|View full text |Cite
|
Sign up to set email alerts
|

Alternation of Sound Location Induces Visual Motion Perception of a Static Object

Abstract: BackgroundAudition provides important cues with regard to stimulus motion although vision may provide the most salient information. It has been reported that a sound of fixed intensity tends to be judged as decreasing in intensity after adaptation to looming visual stimuli or as increasing in intensity after adaptation to receding visual stimuli. This audiovisual interaction in motion aftereffects indicates that there are multimodal contributions to motion perception at early levels of sensory processing. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 13 publications
6
38
0
Order By: Relevance
“…The cue reliability of visual stimuli decreases with increasing distance between a fixation point and visual stimuli (i.e., eccentricity). Indeed, several audiovisual interaction phenomena have been reported under conditions in which visual stimuli were unreliable because of manipulations in eccentricity (e.g., Hidaka et al, 2009;Shams et al, 2002). Following these studies, in the present experiment, relative reliability was manipulated through changes in eccentricity: We investigated the effects of retinal eccentricity (i.e., the difference between the central and peripheral visual fields) on the modulation of visual size by sound.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The cue reliability of visual stimuli decreases with increasing distance between a fixation point and visual stimuli (i.e., eccentricity). Indeed, several audiovisual interaction phenomena have been reported under conditions in which visual stimuli were unreliable because of manipulations in eccentricity (e.g., Hidaka et al, 2009;Shams et al, 2002). Following these studies, in the present experiment, relative reliability was manipulated through changes in eccentricity: We investigated the effects of retinal eccentricity (i.e., the difference between the central and peripheral visual fields) on the modulation of visual size by sound.…”
Section: Methodsmentioning
confidence: 97%
“…That is to say, the changing pitch (ascending or descending) of an auditory stimulus alters the perceived direction of its motion either upward or downward (Maeda, Kanai & Shimojo, 2004). Moreover, the alternation of sound locations leads to the perception of static object movement (Hidaka et al, 2009). Sounds affect the perception of velocity, as well (Kafaligonul & Stoner, 2010;Manabe & Riquimaroux, 2000;Takeshima & Gyoba, 2011).…”
Section: Abstract Multisensory Processing Visual Perception Auditionmentioning
confidence: 99%
“…The effect of vision on sound location is usually robust, whereas the reverse effect-sound attracting visual location-is usually quite subtle and has mostly been observed with visual displays that are difficult to localize (Alais & Burr, 2004b;Bertelson & Radeau, 1981. More recently, though, a particularly clear effect of sound on visual localization has been reported by Hidaka et al (2009;see also Teramoto, Hidaka, Sugita, Sakamoto, Gyoba, Iwaya & Suzuki, 2012). These authors presented a blinking visual stimulus at a fixed location against a nontextured dark background.…”
Section: Spatial Ventriloquism: Immediate Effectmentioning
confidence: 99%
“…Although the effect of audition on vision is perhaps not as widely investigated, striking examples include an experiment by Shams et al (2005) where participants reported seeing multiple flashing objects on a screen, when in fact only one object was flashed, but accompanied by multiple beeps (Shams, Kamitani & Shimojo, 2005). Sound has also been shown to alter the visual perception of object motion (Sekuler, Sekuler & Lau, 1997;Hidaka et al, 2009). Therefore, the role of auditory feedback in driver performance and speed/motion perception cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%
“…As sound is shown to influence visual motion perception (e.g. Hidaka et al, 2009) its attenuation or absence in the car may lead to driver confusion, encouraging drivers to drive faster in order to compensate for the absence of the auditory cues needed for speed perception. Such undesirable increases in driving speed, leading to reduced driver safety may well be intensified by future initiatives to utilise alternate fuel technologies, in lighter, less well shielded vehicles, that present drivers with unfamiliar acoustic environments.…”
Section: Introductionmentioning
confidence: 99%